SAT0187 Immunomodulatory effects of human umbilical cord wharton jelly-derived mesenchymal stem cells (HUCMS) on circulating T-cell subsets in patients with sjögren's syndrome. (23rd January 2014) - Alunno, A.; Montanucci, P.; Bistoni, O.; Basta, G.; Caterbi, S.; Pescara, T.; Bartoloni, E.; Pennoni, I.; Cannarile, F.; Calafiore, R.; Gerli, R.
Abstract : Background: hUCMS are adult stem cells easy to retrieve in bulk. Their immunomodulatory and pro-differentiation properties has been demonstrated. Indeed they may suppress lymphocyte activation, thereby prolonging skin graft survival time. hUCMS may also promote differentiation of tolerizing dendritic cells which favors development of Treg. These properties seem to derive both from hUCMS-secreted soluble factors such as TGFβ and on contact with the target cell. Very few evidences are currently available regarding potential therapeutic application of hUCMS in systemic autoimmune disorders and in particular no data have been published in Sjogren's syndrome (SS) to date. Objectives: We aimed to assess hUCMS immunomodulatory in vitro effects on circulating SS-T cells. Methods: hUCMS were isolated from umbilical cords according to the method that we recently developed and published (1). Five SS patients and 5 healthy donors (HD) were enrolled. Peripheral blood mononuclear cells (PBMC) were obtained by density gradient from SS and HD heparinized venous blood. In selected experiments CD3+ cells were isolated from PBMC by magnetic sorting prior to arrange cultures. Fluorescein diacetate and ethidium bromide and trypan blue dye exclusion assays were performed to assess cell viability. Lymphocytes proliferation was assessed by CFSE diluition assay and culture supernatants were tested for IL-17 with commercial ELISA kit. Intracellular IL-17 was performed by flow cytometry following 6 hours stimulation with PMA, ionomycin and brefeldin. Results: hUCMS and PBMC were successfully co-cultured in CMRL 1066 medium with 10% fetal bovine serum (FBS). When PBMC were used, cell proliferation was dramatically inhibited by hUCMS when co-culture was performed in contact. Interestingly, the higher was PBMC:hUCMS ratio the stronger was such inhibition. IL-17 concentration in supernatants and the percentage of CD4+IL17+ cells were significantly reduced by hUCMS. When magnetic sorted CD3+ cells were used, the proliferation rate was not affected and the effect on IL-17 concentration in supernatants and the percentage of CD4+IL17+ cells was partially lost. Co-cultures in transwell and with microencapsulated hUCMS are currently ongoing. Conclusions: Our preliminary results suggest possible therapeutic applications of hUCMS by selectively targeting Th17 pathogenic cells in SS. References: Montanucci P et al. Tissue Eng Part A 2011 Montanucci P. et al. Biomaterials 2011;32:9254 Disclosure of Interest: None Declared